2021
DOI: 10.1111/jfpp.15504
|View full text |Cite
|
Sign up to set email alerts
|

Combination of precooling with ozone fumigation or low fluctuation of temperature for the quality modifications of postharvest sweet cherries

Abstract: The ozone fumigation device with the self‐circulation function and the low‐temperature fluctuation box with precise temperature control were, respectively, designed to study the effect of the combination of vacuum precooling with ozone fumigation or low‐temperature fluctuation treatment in the quality modifications of sweet cherries during cold storage. The results showed that all the three treatments had a positive effect on quality maintenance. Although precooling combined with low‐temperature fluctuation sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 65 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…In the same way, Alves et al [ 55 ] found that 18 and 14 mg L −1 gaseous ozone applied to strawberries for 30 min were effective in controlling aerobic mesophiles and molds and yeasts, respectively, during 4 days of storage. In studies involving the application of ozone during storage, the exposure of sweet cherries to 2 ppm gaseous ozone for 30 min every 6 days delayed decay development and lowered decay incidence on the fruit for up to 18 days [ 56 ]. As well, treating raspberries with 8–10 ppm O 3 in cycles of 30 min once every 12 h reduced the aerobic mesophilic bacteria and fungi counts on this fruit during 3 days of storage at room temperature [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the same way, Alves et al [ 55 ] found that 18 and 14 mg L −1 gaseous ozone applied to strawberries for 30 min were effective in controlling aerobic mesophiles and molds and yeasts, respectively, during 4 days of storage. In studies involving the application of ozone during storage, the exposure of sweet cherries to 2 ppm gaseous ozone for 30 min every 6 days delayed decay development and lowered decay incidence on the fruit for up to 18 days [ 56 ]. As well, treating raspberries with 8–10 ppm O 3 in cycles of 30 min once every 12 h reduced the aerobic mesophilic bacteria and fungi counts on this fruit during 3 days of storage at room temperature [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Color changes in goji berries were presented in Figure 2a-c values of the three samples treated with AEW+VP were significantly (p ≤ 0.05) higher than those of the control groups, which means brighter coloration of the goji samples. There are several reasons for this trend: first, because the water loss caused by VP occurs on the surface and inside of the goji (Liu et al, 2021), soaking goji berries in AEW followed by VP can effectively slow down water loss in tissue so high L* values were recorded in AEW+VP groups (Dirapan et al, 2021); and second, this change may be related to the increase in antioxidant enzyme activity, which slowed down the senescence of goji so that maintained a high L* value (Patiño et al, 2018) from low respiration rate. Notably, during the entire storage period, there were also no significant differences between AEW+VP-treated samples stored at 4, 7, and 10°C.…”
Section: Appearance and Color Analysismentioning
confidence: 99%